Monitoring plant and soil nitrogen status to predict nitrogen fertilization in corn - Rambo, Lisandro; Silva, Paulo Regis Ferreira da; Strieder, Mércio Luiz; Sangoi, Luís; Bayer, Cimélio; Argenta, Gilber (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to compare the monitoring of corn plant nitrogen status using two indexes of leaf relative chlorophyll content (critical leaf relative chlorophyll content – CRCC and sufficiency index – SI) determinated by chlorophyll meter and to evaluate the integration between plant and soil characteristics for monitoring the N content of the soil-plant system in corn. Two field experiments were conducted in Eldorado do Sul, State of Rio Grande do Sul, Brazil. The treatments were different N management systems, with different N application times and N rates, carried out with or without monitoring. In the monitored systems, CRCC and SI were used to indicate when N side-dress should be performed and it was tested, using the CRCC and soil nitrate content, one integrated monitoring system. Grain yield and grain yield increase, gross profit increase and the technical, economic and N use efficiency were often higher in the monitored systems than in the systems without monitoring. The efficiency of the monitoring methods, using the CRCC and using the SI and integrating the CRCC and soil nitrate content, was similar. Monitoring corn N status integrating the CRCC and soil nitrate content did not improve nitrogen use efficiency in the tested environment.